Retraction notice to "TRANSITIVITY AND PERSONIFICATION IN INDONESIAN POPULAR NOVEL LASKAR PELANGI" [Jurnal Pendidikan Ilmu Pengetahuan Sosial Vol 30 No 2 December 2021 page 161-178] (https://doi.org/10.17509/jpis.v30i2.37500) - Yuliana, Rini; Santosa, Riyadi; Sumarlam, Sumarlam; Wiratno, Tri (Jurnal Pendidikan Ilmu Sosial, 2022)
This article (R Yuliana 2021a) has been withdrawn as requested by the author during the production system period. Therefore, on behalf of the publisher of the journal, I would like to apologize to both authors and readers for the inconvenience.